2016
DOI: 10.1371/journal.pone.0157866
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Landscape of Human Breast Cancer Cells in Response to Dietary Compound Resveratrol

Abstract: Aberrant DNA methylation is a frequent epigenetic alteration in cancer cells that has emerged as a pivotal mechanism for tumorigenesis. Accordingly, novel therapies targeting the epigenome are being explored with the aim to restore normal DNA methylation patterns on oncogenes and tumor suppressor genes. A limited number of studies indicate that dietary compound resveratrol modulates DNA methylation of several cancer-related genes; however a complete view of changes in methylome by resveratrol has not been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…As shown in Table 6, multiple drugs were identified that had a significantly anticorrelating gene pattern to that induced by CDH2/4/6/17. For instance, resveratrol and its derivatives had been reported to exhibit anticancer activity in TNBC cells possibly through interfering with epigenetic regulation [53, 54]. Thus, our findings provided additional evidence to support the claim that the affected pathways were induced by CDH2/4/6/17 and revealed that the perturbagens predicted here might be used to target TNBC with the alterations of CDH2/4/6/17-SC-TFs axis.…”
Section: Resultssupporting
confidence: 81%
“…As shown in Table 6, multiple drugs were identified that had a significantly anticorrelating gene pattern to that induced by CDH2/4/6/17. For instance, resveratrol and its derivatives had been reported to exhibit anticancer activity in TNBC cells possibly through interfering with epigenetic regulation [53, 54]. Thus, our findings provided additional evidence to support the claim that the affected pathways were induced by CDH2/4/6/17 and revealed that the perturbagens predicted here might be used to target TNBC with the alterations of CDH2/4/6/17-SC-TFs axis.…”
Section: Resultssupporting
confidence: 81%
“…Similar findings have been reported in trials examining the ability of resveratrol to reduce homocysteine levels. Resveratrol significantly decreased serum levels of homocysteine in rats on a methionine-rich diet [ 291 , 292 ], and preferentially affected the methylation status of cancer cells [ 292 , 293 , 294 ]. However, despite extensive trials, resveratrol failed to inhibit aging-associated pathologies or extend the lifespan in mammals [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Nutrients and Their Metabolites And Enzymes Related To Dnmentioning
confidence: 99%
“…Resveratrol, a natural product found in red grapes and wine, is one of the most common dietary flavonoids. Except antioxidant and anti-inflammatory effect as reported, recent studies have demonstrated that resveratrol exerted antitumor effects on a panel of human cancers, such as breast (18), colon (19), ovarian (20), lung (21) and prostate cancer (22). Mechanism investigation manifested that multiple signaling pathways and mechanisms are involved in the antitumor activity of resveratrol, including suppression of various protein kinases, such as Akt, ERK and EGFR, induction of cell cycle arrest or apoptosis, and inhibition of cell migration and metastasis (23).…”
Section: Resveratrol Suppresses Human Hepatocellular Carcinoma Via Tamentioning
confidence: 91%